Hotel management and operations (Wiley, 2011)
Hotel Management and Operations, Fifth Edition provides a practical, up-to-date, and comprehensive approach to how professionals across the industry manage different departments within their operation. From the front office to finance, from marketing to housekeeping, this resource offers advanced theory played out in practical problems.